Responding to Allegations of Subsidy Violations: Indonesia's Compliance under the Agreement on Subsidies and Countervailing Measures - Kholik, Nur; Hidayat, Wahyu; Asyrafi, Muhammad (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Indonesia frequently finds itself confronted with allegations of subsidy infractions from European and Western counterparts. Thus, the focal point of this analysis revolves around the accusations leveled by the United States and the European Union against Indonesia for purported subsidy transgressions, along with an exploration of the strategic measures implemented by Indonesia to address and rectify these claims.Purpose/Objective Study: This examination scrutinizes the contentions posited by both the United States and the European Union concerning subsidies and anti-dumping activities attributed to the Indonesian Government. Additionally, it delves into the remedial measures undertaken by the Indonesian Government in response to these allegations.Design/Methodology/Approach: This study constitutes normative legal research, employing a case-centric methodology to scrutinize allegations of subsidy violations leveled against Indonesia by both the United States and the European Union. The analytical approach adopted involves employing descriptive analysis techniques to illuminate the intricacies of the legal landscape underpinning the accusations.Findings: This scholarly analysis posits that, in response to accusations from the United States, Indonesia should actively pursue "sympathetic consideration" through the diplomatic avenue of bilateral dispute resolution, particularly concerning matters pertaining to the GATT's implementation. Furthermore, in the face of legal challenges from the European Union, Indonesia is compelled to furnish compelling evidence and articulate substantiated justifications grounded in the outcomes of its non-renewable natural resource assessments. This research discerns that Indonesia, positioned as a developing nation, is accorded protective measures under the auspices of Article 8.19 DSU, Article 12.11, Article 21.8, and Article 27.2. Specifically, Indonesia retains the legitimate authority to curtail nickel ore exports in accordance with the provisions delineated in the 1994 GATT. This prerogative is exercised to shield against and avert the depletion of Indonesia's natural resources, a concern underscored by Article 20 of the 1994 GATT, recognizing the potential for these resources to reach a state of extinction. Paper Type: Research Article